Spin dynamics in the antiferromagnetic phases of the Dirac metals AMnBi2 (A = Sr, Ca) - Rahn, M; Princep, A; Piovano, A; Kulda, J; Guo, Y; Shi, Y; Boothroyd, A (American Physical Society, 2017)
The square Bi layers in AMnBi2 (A= Sr, Ca) host Dirac fermions which coexist with antiferromagnetic order on the Mn sublattice below TN=290 K (Sr) and 265 K (Ca). We have measured the spin-wave dispersion in these materials by triple-axis neutron spectroscopy. The spectra show pronounced spin gaps of 10.2(2)meV (Sr) and 8.3(8)meV (Ca) and extend to a maximum energy transfer of 61-63 meV. The observed spectra can be accurately reproduced by linear spin-wave theory from a Heisenberg effective spin Hamiltonian. Detailed global fits of the full magnon dispersion are used to determine the in-plane and interlayer exchange parameters as well as well as the magnetocrystalline anisotropy constant. To within experimental error we find no evidence that the magnetic dynamics are influenced by the Dirac fermions.